Lateral heterogeneity and domain formation in cellular membranes. (October 2020) - Kinnun, Jacob J.; Bolmatov, Dima; Lavrentovich, Maxim O.; Katsaras, John
Highlights: Review article describing recent experimental and theoretical membrane lateral heterogeneity research. Describes the static and dynamic physical concepts behind domain formation in model membranes. Describes coarse-grained, phenomenological approaches that result in phases associated with lipid lateral heterogeneity. Abstract: As early as the development of the fluid mosaic model for cellular membranes, researchers began observing the telltale signs of lateral heterogeneity. Over the decades this has led to the development of the lipid raft hypothesis and the ensuing controversy that has unfolded, as a result. Here, we review the physical concepts behind domain formation in lipid membranes, both of their structural and dynamic origins. This, then leads into a discussion of coarse-grained, phenomenological approaches that describe the wide range of phases associated with lipid lateral heterogeneity. We use these physical concepts to describe the interaction between raft-lipid species, such as long-chain saturated lipids, sphingomyelin, and cholesterol, and non-raft forming lipids, such as those with short acyl chains or unsaturated fatty acids. While debate has persisted on the biological relevance of lipid domains, recent research, described here, continues to identify biological roles for rafts and new experimental approaches have revealed the existence of lipid domains in living systems. Given the recent progress on both the biological and structural aspects of raft formation, the research area of membrane lateral heterogeneity will not only expand, but will continue to produce exciting results.